Study of the effects of sludge discharge from water treatment plants to the municipal wastewater network and its effect on the wastewater treatment process - pouneh Abdolahi Salari; Sina Fard Moradinia (علوم محیطی)
Introduction: Today, with the development of water treatment plants, sludge management has become one of the most important environmental issues that can be both a threat and an opportunity. Therefore, due to the increasing development of water treatment plants in the country and the production of a significant amount of sludge, it is necessary to take measures. Material and methods: In this research, cationic polyelectrolyte and anionic polyelectrolyte of industrial grade from Basf company, Germany, polyaluminum chloride (AL2 (OH) n CL6) with industrial grade from Chinese company, ferric chloride (FeCl3) in industrial grade from Fanavaran Aria Mehvar company, ferric chloride (FeCl3) in industrial grade from Merc Germany, and aluminum sulfate (Al2(SO4)3) in industrial grade from Kimia Exir were purchased and used. The jar test was used to determine the appropriate type and amount of coagulants. In this experiment, sixglass containers and a stirrer were used to stir the contents of all the containers at the same time. One liter of the sample with pre-determined turbidity was added to each container. First, the mixer was set to a high speed of 200 rpm. Then for each coagulant, a certain range of it is added to the dishes at the same time and was mixed at 200 rpm for one minute. In the next step, the stirrer was placed on a slow speed of 20 rpm for 15 minutes, and finally the solutions were allowed to settle for 30 seconds and the turbidity of the top layer was measured. To compare sedimentation by coagulant and flocculant, 2% (w/v)of coagulant and flocculant were prepared and equal volume of each one was added to the sludge sample from Maragheh water treatment plant to improve the performance of materials in acidic and alkaline environments. . By creating acidic and equal alkaline environments for all samples, half-hour sedimentation was measured. To observe more sedimentation and compare the samples, 1, 2 and 3 hour sedimentation was also measured. In the last experiment, which was performed without coagulant and it was done just by raising the Tss and mixing with the sewage sludge, more settling time was given and a very good result was obtained. ​​Maragheh city is one of the environs of Tabriz. In this research, it was necessary to select an area which firstly had a water treatment plant and secondly had a wastewater treatment plant, which was possible in Maragheh city. Maragheh water treatment plant is located next to Sufi River dam and coagulant materials are used to treat drinking water in this city. The wastewater treatment plant of this city has two phases, which according to our need for the first settling sludge to increase the TSS, the first phase of this treatment plant was sampled and tested.Results and discussion: In this study, the methods of reducing sludge from water coagulation using various coagulants and flocculants and changing their ratio in acidic and alkaline environments were evaluated. Also, coagulation of sludge from water treatment plants by raising TSS was investigated using initial sewage sludge containing detachable municipal wastewater solids. We also tried to evaluate the volume of sludge produced, the amount of ion removal, and the amount of residual ions by selecting different coagulants and changing their ratios. Sampling was done periodically from Maragheh water treatment plant and Maragheh wastewater treatment plant. In the experiment related to the mixture of sludge from the water treatment plant and sludge from initial sedimentation of sanitary wastewater treatment plant, ideal results were obtained so that the coagulation volume reached more than 50% and with increasing retention time, this efficiency increased by more than 70%. For 5 hours, the amount of sediment was only 80 ml, and 420 units had been deposited. The gelatinous sludge in the water treatment sludge, which is due to aluminum hydroxides and compounds of other coagulants with sludge, makes further dehydration impossible, and despite the increase in coagulant and the use of other coagulants, no good dewatering was performed. In order to obtain better results experiments were performed in acidic and alkaline environments to examine the extent of sludge reduction. In practice, in these environments, good results were not obtained and setteling failed‌ , such as in neutral medium experiments, Conclusion: According to the results of the experiments, it can be concluded that without any cost of materials, by giving time for settling, mixing the two types of sludge and using a variety of sludge drying methods, dewatering of this jelly sludge is possible. If this is done, surface water pollution will be prevented and the problem of disposing of this sludge will be practically eliminated.